2017
DOI: 10.31357/jtfe.v7i1.3022
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and Nitrogen Release Patterns of Parkiabiglobosa and Albizialebbeck Leaves with Nitrogen Fertilizer for Maize Production in Sudan Savanna Alfisolof Nigeria

Abstract: Biomass transfer or cultivation of leguminous trees has higher eco-friendly profiles for soil nutrients restoration especially nitrogen. The research is conducted on decomposition and nitrogen release patterns of Parkia biglobosa and Albizia lebbeck leaves with nitrogen fertilizer for maize production in sudan savannah alfisol of Nigeria. Data were analysed using (ANOVA). 56 % of N in the litter bag was released the first two weeks of biomass incubation and progressively increases weeks after planting. Decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Among the plant species, however, grain yield was highest in Albizia amended plots in both year 1 and 2 (Table 6). This confirms an earlier study in Nigeria by Oyebamiji et al (2017) who showed that Albizia decomposed and mineralized N faster for maize uptake and improve yield under Semi-humid/arid environment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the plant species, however, grain yield was highest in Albizia amended plots in both year 1 and 2 (Table 6). This confirms an earlier study in Nigeria by Oyebamiji et al (2017) who showed that Albizia decomposed and mineralized N faster for maize uptake and improve yield under Semi-humid/arid environment.…”
Section: Discussionsupporting
confidence: 91%
“…In general, maize yield was higher in amended plots compared to the control; likewise, higher yield was recorded in year 2 than in year 1 (Table 6). This observation reiterates the important role that biomass from leguminous plants play in releasing N to improve soil organic matter quality and increase crop yield (Li et al, 2018;Oyebamiji et al, 2017). Similar to the findings of Haider et al (1991) there was a strong relationship between microbial biomass, N mineralization and maize grain yield in both cropping years (Table 6).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Cellulose content in litter ranged from 4.11 to 11.84%, that of lignins from 2.28 to 8.12%, that of NDF from 21.35 to 77.73, and that of phenolic compounds from 0.47 to 16.11%. These values were average relative to those reported by previous studies in the different savannahs [4,63], except for the phenol content which was among the highest values. Indeed, Mapongmetsem [5] reported for 8 plant species of Adamawa savannahs, cellulose, lignin, NDF and phenolic compound contents were very low compared to ours.…”
Section: Litter Organic Compound Contentssupporting
confidence: 46%
“…Mitchell et al [4] found in their litter production studies that the lignin content ranged from 1.73 to 3.60% for three species (Proteoid, Ericoid and Restiod) of savannahs of South Africa. Oyebamiji et al [63] also reported values from 8.24 to 11.06% for lignin and from 0.57 to 0.75% for phenolic compounds in the litter of Albizia lebbeck and Parkia biglobosa in the savannahs of Nigeria. The litter of Jatropha curcas contains a lignin content of 12.03% according to Abugre et al [64].…”
Section: Litter Organic Compound Contentsmentioning
confidence: 95%